1980
DOI: 10.1159/000122968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovariectomy on Plasma LH, FSH, Estradiol, and Progesterone and Medial Basal Hypothalamic LHRH Concentrations in Old and Young Rats

Abstract: Resting plasma concentrations of LH, FSH, estradiol, and progesterone and medial basal hypothalamic concentrations of LHRH (MBH-LHRH) were measured by RIA in 8- to 12-month-old female rats which had begun to exhibit constant estrous (CE) or prolonged diestrous (PD) vaginal smear patterns and compared to young cycling rats on proestrus, estrus, or diestrus. In addition, we examined the effect of ovariectomy on these hormonal profiles. Old CE rats have normal plasma LH, FSH and progesterone concentrations, but e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2
3

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 10 publications
2
50
2
3
Order By: Relevance
“…As aforementioned, the adding of a preceding extraction step generally halved the concentrations measured, which for the native rats in this study gave concentrations that do not agree with what has been seen in previous studies where conventional extraction RIAs have been used [26][27][28][29]. This suggests that the commercial RIAs tested in the current study are not suited for pre-analysis extraction, at least not using the method used in the present study.…”
Section: Sample Extractioncontrasting
confidence: 47%
See 1 more Smart Citation
“…As aforementioned, the adding of a preceding extraction step generally halved the concentrations measured, which for the native rats in this study gave concentrations that do not agree with what has been seen in previous studies where conventional extraction RIAs have been used [26][27][28][29]. This suggests that the commercial RIAs tested in the current study are not suited for pre-analysis extraction, at least not using the method used in the present study.…”
Section: Sample Extractioncontrasting
confidence: 47%
“…Of the RIA kits from DPC, DSL and MPB tested, MPB rendered the highest concentrations of 17β-estradiol and DSL the lowest. Using the DPC kit to measure unextracted samples resulted in 17β-estradiol concentrations in the native rats that best resembled concentrations observed in earlier studies where conventional RIAs, including an extraction step, have been used [26][27][28][29]. The differences in concentrations measured by the kits were indeed large enough to complicate comparisons between studies where kits from different companies are used.…”
Section: Discussionmentioning
confidence: 56%
“…LH is secreted from the anterior pituitary and E normally exerts negative feedback inhibition of LH release. Removal of E by ovx causes a subsequent increase in serum LH and replacement with estradiol lowers LH (Freeman et al, 1976;Wise and Ratner, 1980). The role of LH in ovxed animals has not been addressed in studies that have examined E's effect on spatial memory.…”
Section: Introductionmentioning
confidence: 99%
“…We allowed the rats to recover from the surgery for a week. This helped to decrease the residual ovarian hormone levels in the system before retesting the effectiveness of the anesthesia 13,15 . We recorded the estrous cycles daily until the day of the experiment ( Table 2).…”
Section: Study 2: Effect Of Tbe-mt In Ovariectomized Ratsmentioning
confidence: 99%
“…Having previously shown that a TBE-MT combination is effective in male rats 7 , we extended the investigation to determine the efficacy of the drug combination in female rats and test whether it would interfere with the estrous cycle. We also monitored the effectiveness of the TBE-MT combination in ovariectomized rats (where estrogen and progesterone levels are significantly lower [13][14][15] ).…”
mentioning
confidence: 99%